Sexual reproduction and biometry of the non-zooxanthellate papillose cup coral Paracyathus pulchellus - Marchini, Chiara; Fossati, Valentina; Cerpelloni, Martina; Caroselli, Erik; Falini, Giuseppe; Dubinsky, Zvy; Goffredo, Stefano (Frontiers in Marine Science, 2022)
Basic information on the reproductive biology of many scleractinian corals species is limited or entirely lacking, particularly from temperate zones, though it is essential for a better understanding of their ecology. This study describes the morphological aspects of gametogenesis and biometric parameters of the papillose cup coral Paracyathus pulchellus collected at Palinuro (Italy, Southern Tyrrhenian Sea), filling a knowledge gap about the reproductive biology and growth of a widespread Mediterranean and Northern Atlantic coral. Samples of P. pulchellus were collected by SCUBA diving between 5- and 10-meters depth during 18 monthly collections from June 2010 to December 2011. Sexually active polyps displayed either oocytes or spermaries, indicating that P. pulchellus was gonochoric. The sex ratio of sexually active polyps was 1:1. Gametogenesis began with undifferentiated germ cells arose in the gastrodermis that migrated towards the mesoglea of the mesentery where they completed the development. During spermatogenesis, spermary diameter increased from 25 to 83 µm. Oocyte diameter ranged from 9 to 146 µm and during oogenesis the nucleus/cytoplasm ratio decreased due to the accumulation of yolk. The nucleus migrated to the periphery of the oocyte adhering closely to the cell membrane. No embryo was observed in the coelenteric cavity of the polyps, suggesting an external development of planktotrophic larvae due to the small-sized mature oocytes and a possible broadcast spawning reproductive mode. Gonadal index of both females and males increased significantly from August until November and fertilization took place from November to January. Only sexually inactive individuals were observed from February to April, suggesting a quiescence period in both males and females. Seasonal variations in water temperature and photoperiod may have a key role in regulating gametogenesis. The analysis of the main biometric parameters (polyp width, height, dry skeletal mass, volume, surface/volume ratio and bulk skeletal density) showed a negative correlation between size and skeletal density, and no sexual dimorphism.